A Case Study on Demodicosis in Golden Retriever - Pradhan, F.; Paudel, S (NPI Journal of Science and Technology, 2024)
A six-year-old Golden Retriever dog with a history of alopecia, itching, scratching and erythema all over the body was presented to Veterinary Teaching Hospital, Nepal Polytechnic Institute, Chitwan, Nepal. Dog weighed 44.6 kg was golden brown in colour. On clinical examination mucous membrane, temperature, Heart rate was normal. The eczematous lesions were erythematous and alopecia was seen in the area surrounding the lesions. The case was suspected of parasitic skin infection, and skin scrapping was taken from different affected area until there was a capillary bleeding with the help of scalpel blade after moistening the skin with glycerin. The scraping was treated with 10% KOH until it was submerged after that the solution was gently heated and the supernatant was discarded, and remnants were transferred to slide. A cover slip was placed, and it was examined first under the low power then high power for detail study. Demodex was observed under microscopic examination. The case was diagnosed as patchy demodex infestation with secondary bacterial infection. The lesions were cleaned by medicated ketachonazole shampoo and systemic administration of fixotic advance and Amoxicillin clavunate 375 mg antibiotic was given for secondary bacterial infection. After 2 weeks skin scrapping test was again performed and found negative. There were no red rashes and lesions were slowly healing.